STRENGTHENING HUMAN RESOURCE MANAGEMENT AT CIHERANG VILLAGE TOURISM DESTINATIONS, SUMEDANG REGENCY - Yulianah Yulianah; Supardi Supardi (SEAN Institute, 2022)
The COVID-19 epidemic has significantly impacted a variety of industries, including the travel and tourism industry. The tourism industry is truly the one that is harmed the most when there are limits on activities that take place outside. The purpose of this study is to improve human resources, particularly in regard to the management of the tourism object located in Kampung Ciherang Tanjung Sari, which is located in the Sumedang Regency. The data and information acquired is then processed once more with TOWS analysis. The findings of the analysis show that there are sufficient resources and good cooperation between Perhutani, LPI, and the local community in the management of attractions. In spite of this, it is indisputable that there are still a variety of facets that, in aggregate, need to be enhanced, beginning with the consolidation of capital, the maintenance of effective human resource management, and the addition of a venue for pupils.